2017
DOI: 10.1002/er.3907
|View full text |Cite
|
Sign up to set email alerts
|

Effect of high irradiation on photovoltaic power and energy

Abstract: Summary Solar photovoltaics (PV) is a promising solution to combat against energy crisis and environmental pollution. However, the high manufacturing cost of solar cells along with the huge area required for well‐sized PV power plants are the two major issues for the sustainable expansion of this technology. Concentrator technology is one of the solutions of the abovementioned problem. As concentrating the solar radiation over a single cell is now a proven technology, so attempt has been made in this article t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
42
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(42 citation statements)
references
References 44 publications
0
42
0
Order By: Relevance
“…Also, MPPT systems are responsible for injecting maximum power into the circuit. During high irradiation intensity, increased power on the input side may cause false tripping of over-current relays [8,9]. In addition, non-linear characteristics of PV array makes it difficult to attain a decision boundary for the faulty condition [10].…”
Section: Introductionmentioning
confidence: 99%
“…Also, MPPT systems are responsible for injecting maximum power into the circuit. During high irradiation intensity, increased power on the input side may cause false tripping of over-current relays [8,9]. In addition, non-linear characteristics of PV array makes it difficult to attain a decision boundary for the faulty condition [10].…”
Section: Introductionmentioning
confidence: 99%
“…The three most important environmental parameters that affect the power output of PV modules are solar irradiance, (ambient) temperature, and dust accumulation on the modules [7][8][9][10]. For several forecast models that are used to predict the power output of PV power plants, a wider number of parameters are used including air mass, solar spectrum, ambient temperature, wind speed and dust soiling factor [11].…”
Section: Review Of Literaturementioning
confidence: 99%
“…Studying the performance evaluation of solar water pumping system, was observed that power output from the solar array increases as solar intensity increases [80]. Also, the performance of PV water pump mainly depends on the water flow rate which is influenced by weather conditions at the location, especially solar irradiance and air temperature variations [81].…”
Section: Solar Pv Pumping Performancementioning
confidence: 99%